Empatic Budgeting Model: Study of Regional Budgeting In Tana Toraja Regency - Pasoloran, Oktavianus; Kurniasari Wibisono, Lisa (Devotion : Journal of Research and Community Service, 2022)
This study aims to produce empathic budgeting models that are built through the concept of altruism. With this model, regional budgets are built into a result of social construction that is full of values, empowering, emancipatory, and that regional budgeting is dedicated to the welfare of the community. This study uses a content analysis approach to find out or explain the content of community interests in the regional budgeting of Tana Toraja Regency. The results of this study indicate that; (1) the formulation of the vision and mission shows clear content regarding the orientation of community welfare, but in the regional planning process the orientation towards community interests is decreasing. The musrembang process, which is expected to encourage community participation and needs, has to deal with the inability of regional funding, which is mostly allocated for personnel expenditures, goods and services, and other asset expenditures. (2) the regional budget budgeting model should be oriented along lines that are more emancipatory and empowering by prioritizing several ways in which "community welfare" is its basic objective. Budgetary actors who are involved in the regional budgeting process must have "feeling in" empathy which is done by entering into the emotional state (feelings) of the community through a deeper understanding of the community's condition. Thus the empathic budgeting model is expected to provide broad implications in understanding community orientation in regional budgeting